Exploring the Potential of Dynamic Perspective Taking on Business Processes - Krenn, Florian; Stary, Christian (Complex Systems Informatics and Modeling Quarterly, 2016)
Although many organizations have started to work with business process models in their operational practice, they have not explored the entire potential of intertwining business process modeling with organizational development. Process specifications contain workflows that require execution, in order to achieve business objectives and support business operation effectively. With the advent of Subject-oriented and Social Business Process Management, communication and stakeholder interaction have become novel perspectives on how to design and implement processes. They go beyond formal responsibilities encoded in functional roles, and are not very common across organizational hierarchies. However, stakeholders, including organizational developers and IT specialists, can be supported looking at processes and their execution from either perspective, namely, from a traditional one, focusing on functions and task accomplishment, and from an interactional perspective, focusing on communication among stakeholders and system interactions. The introduced dual-mode workflow execution engine UeberFlow allows considering both perspectives during process runtime, thus, checking operational completeness from either perspective. Stakeholders can start modeling with a perspective they are familiar with and subsequently proceed with the another one by switching dynamically to an alternate mode of execution. The presented meta-model and architecture of such a dual mode support tool enables coupling business process management directly with organizational development.